Analisis Sebaran Tempat Penampungan Sampah Menggunakan Sistem Informasi Geografis dan Dampaknya Terhadap Lingkungan Masyarakat - Annursyah Bachtiar; Sukri Nyompa; Hasriyanti Hasriyanti; Uca Sideng; Amal Arfan (Jurnal Penelitian Pendidikan Geografi, 2025)
Waste problems are one of the major problems in Indonesia, as is the case with Somba Opu Sub-district, Gowa Regency, which is inseparable from waste problems. Mapping the distribution of garbage dump using Geographic Information Systems is a solution to overcome this problem. The objectives of the study were to determine the distribution of garbage dump locations in Somba Opu Sub-district, analyze the suitability of land used as garbage dump land, and identify the community environmental impacts caused by the presence of garbage dump. The method used is Mixed Method Explanatory Sequantial Design. The results of the research on the distribution of garbage dump locations in Somba Opu Sub-district were 23 points. Analysis of data processing results through the Average Nearest Neighbor method is a uniform pattern (dispersed) 1.464325. The results of overlaying the distance to rivers, roads, and settlements there is a classification of land suitability of garbage dump Somba Opu District, namely; 6 (26,1%) locations are not suitable, 10 (43,5%) locations are less suitable, 3 (13,0%) locations are suitable, and 4 (17,4%) locations are very suitable. The responses of people living within a 500 meters radius of the garbage dump indicate that waste management has positive and negative impacts on health, the environment, and social and economic life.